2021
DOI: 10.3390/met11081299
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Tension-Compression Asymmetry of Extruded Ti-6.5Al-2Zr-1Mo-1V under Quasi-Static Conditions at High Temperature

Abstract: The tension-compression asymmetry (TCA) behavior of an extruded titanium alloy at high temperatures has been investigated experimentally in this study. Uniaxial tensile and compressive tests were conducted from 923 to 1023 K with various strain rates under quasi-static conditions. The corresponding yield stress and asymmetric strain hardening behavior were obtained and analyzed. In addition, the microstructure at different temperatures and stress states indicates that the extruded TA15 profile exhibits a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It was found that pre-strain of 0.05 enhanced flow stress and elongation in tensile tests at a temperature of 850 • C. Moreover, pre-strain promoted dynamic recrystallization by increasing the deformation substructure. Zhang et al [4] analyzed the asymmetry of tension-compression behavior of an extruded Ti-6.5Al-2Zr-1Mo-1V alloy (TA15) at a temperature range of 650-750 • C. The corresponding yield stress and asymmetric strain hardening behavior were studied.…”
Section: Deformation Behaviormentioning
confidence: 99%
“…It was found that pre-strain of 0.05 enhanced flow stress and elongation in tensile tests at a temperature of 850 • C. Moreover, pre-strain promoted dynamic recrystallization by increasing the deformation substructure. Zhang et al [4] analyzed the asymmetry of tension-compression behavior of an extruded Ti-6.5Al-2Zr-1Mo-1V alloy (TA15) at a temperature range of 650-750 • C. The corresponding yield stress and asymmetric strain hardening behavior were studied.…”
Section: Deformation Behaviormentioning
confidence: 99%